The 'poor man's' Landers lens. Issue 10 (October 1988) - Benjamin, L
Abstract : A clinical application of the technique of 'autoindirect ophthalmoscopy' in a gas-filled, phakic eye is described. Peroperative photographs obtained by this technique are demonstrated and the optics described.